Impacts of inclined plate on melting time for phase change material filled blocks: Experimental and numerical analysis - Öztop, Hakan Fehmi; Gur, Muhammed; Selimefendigil, Fatih; Cosanay, Hakan (Elsevier, 2024)
This study investigates the impact of inclined plates on the melting time of phase change material (PCM)-filled blocks in a channel under turbulent airflow, considering different velocities. The primary objective is to analyse how inclined plates influence the melting process and the time required for complete melting of PCM blocks. Both experimental and numerical approaches are employed using the finite volume method to solve two dimensional time-dependent governing equations. The Reynolds numbers are varied at 40000, 50000, and 60000, while the inclination angle of the plate ranges from alpha = 110 degrees to 130 degrees. RT25HC is selected as the PCM. The findings reveal that inclined plates effectively regulate PCM cube melting times within a block, influencing the flow field and temperature distribution in the channel. Notably, both experimental and numerical results consistently highlight the alpha = 110 degrees inclination angle as the most effective among the considered angles.
Keywords: Experimental; Square Flow Channel; Heat Transfer Enhancement; CFD; Thermal Energy Storage; Phase Change Material